2022
DOI: 10.7861/clinmed.2021-0522
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 infection causing residual gastrointestinal symptoms – a single UK centre case series

Abstract: Although COVID-19 was first recognised as an acute respiratory illness, extra-pulmonary manifestations are increasingly being recognised. Acute gastrointestinal side effects have been well reported with COVID-19 infection and are estimated to affect around 17% of patients. With COVID-19 still being a relatively new illness, the chronic gastrointestinal symptoms are less well characterised. Post-infectious irritable bowel syndrome (IBS) can occur following bacterial and viral infections, and with ACE-2 receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 18 publications
2
20
0
2
Order By: Relevance
“…We read with great interest the article by Blackett and colleagues 1 with abdominal pain (29.2%), diarrhea (18.8%), constipation (10.4%), nausea (10.4%), and dyspepsia (29.2%) being the most commonly reported symptoms. 2 Of our responders, 39.1% were troubled by these symptoms every day; which would be compatible with Rome IV IBS diagnostic criteria. 5 A recent Nature review article by Meringer and Mehandru 6 has further supported this phenomenon, as a "post-acute COVID-19 syndrome"; offering an overview of various potential mechanisms for its pathogenesis, including persistent inflammation, autoimmunity, persistence of viral antigen, altered cytokine production, prior mental health condition, maladaptive neuro-immune interactions, and alteration to the fecal microbiome.…”
Section: Post-covid-19 Irritable Bowel Syndromesupporting
confidence: 68%
See 2 more Smart Citations
“…We read with great interest the article by Blackett and colleagues 1 with abdominal pain (29.2%), diarrhea (18.8%), constipation (10.4%), nausea (10.4%), and dyspepsia (29.2%) being the most commonly reported symptoms. 2 Of our responders, 39.1% were troubled by these symptoms every day; which would be compatible with Rome IV IBS diagnostic criteria. 5 A recent Nature review article by Meringer and Mehandru 6 has further supported this phenomenon, as a "post-acute COVID-19 syndrome"; offering an overview of various potential mechanisms for its pathogenesis, including persistent inflammation, autoimmunity, persistence of viral antigen, altered cytokine production, prior mental health condition, maladaptive neuro-immune interactions, and alteration to the fecal microbiome.…”
Section: Post-covid-19 Irritable Bowel Syndromesupporting
confidence: 68%
“…Our prospective survey study examined the long‐term GI effects and showed that 43.8% of responders had new persistent GI symptoms at 6 months following their PCR diagnosis of COVID‐19; with abdominal pain (29.2%), diarrhea (18.8%), constipation (10.4%), nausea (10.4%), and dyspepsia (29.2%) being the most commonly reported symptoms. 2 Of our responders, 39.1% were troubled by these symptoms every day; which would be compatible with Rome IV IBS diagnostic criteria. 5 …”
supporting
confidence: 68%
See 1 more Smart Citation
“…Cooney et al did not analyze their patients with the Rome IV criteria questionnaire, which makes it impossible to refer to and compare with our results. In the conclusions, the authors stated that additional studies are urgently needed to further confirm the hypothesis of IBS after COVID-19 [20].…”
Section: Discussionmentioning
confidence: 95%
“…As we previously reported, an impaired gut barrier and microbial alterations may lead or be associated with gastrointestinal [ 54 ], mental [ 137 ], and metabolic [ 138 ] symptoms or disorders. Cooney et al reported that gastrointestinal symptoms were common at 6 months among 43.8% individuals post COVID-19 disease [ 139 ]. Ours, yet unpublished data of a cohort of COVID-19 individuals in Poland, supports previous reports of a high percentage of patients with GI symptoms following COVID-19 recovery.…”
Section: Special Clinical Situationsmentioning
confidence: 99%